Visual recursion without recursive language? a case study of a minimally verbal autistic child - Rosselló, Joana; Celma-Miralles, Alexandre; Martins, Mauricio Dias (Frontiers in Psychiatry, 2025)
The human faculty to generate an infinite set of structured expressions in language, present in most cultures and normal ontogeny, is the most substantial evidence of the human capacity for recursion. In contrast, strong evidence of this capacity in other domains has been sparse, inviting the speculation that recursion is primarily linguistic and co-opted into other domains. Here, we present a case report of a minimally verbal 11-y.o. autistic child with poor language comprehension whose speech rarely exceeds two-word commands despite remarkable hyperlexia (i.e., mechanical reading in Spanish, Catalan, and English) and a visually-based, mainly nominal lexicon acquired through reading. Importantly, medium-range scores in visual tasks and hyperlexia suggest that he can detect complex visual patterns despite low fluid intelligence. Against this background, we tested whether this child could represent recursive hierarchical embedding in vision, despite no evidence of it in language. We found that 1) his accuracy was above chance and 2) it was not significantly different from that of typically developing children. Accordingly, we suggest that a core capacity of recursion, interfacing with a sensory modality and a visuospatial conceptual system, is sufficient to process recursive patterns in vision. In contrast, linguistic recursion may require more complex sensorimotor and conceptual-intentional machinery.